Debriefing, a dialogical space for the development of reflective thinking in nursing - Saionara Nunes de Oliveira; Jussara Gue Martini; Jaime Alonso Caravaca-Morera; Marta Lenise do Prado; Bruna Pedroso Canever; Carina Bortolato-Major; Neide da Silva Knihs (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To understand the pedagogical elements necessary for the debriefing to favor the development of reflective thinking. Method: A single case study developed at the Centro de Simulación en Salud of the Escuela de Enfermería of the Universidad de Costa Rica in October 2018. Data were collected through interviews, observation and document analysis. For data analysis, the strategy of theoretical propositions and the construction of explanation technique were used. Results: The data originated two categories: 1) pedagogy of the organization, addressed elements thought by the professor to facilitate the dialogue; 2) facilitation pedagogy, brought elements from the dialogue itself that enrich the discussion, mobilize the group, provoke reflection and engagement. Final considerations: It is essential to include the following as pedagogical elements in order to favor the development of reflective thinking: prior planning, adequate environment, systematization, pedagogical training in facilitating debriefing, openness to dialogue, pedagogical respect, valorization of positive aspects, patience, and motivation.